World Federation of Neurosurgical Societies Young Neurosurgeons Survey: An Assessment of the Global Neurosurgery Research Environment, Capacity, Output and Barriers - Thango, Nqobile S.; Baticulon, Ronnie E.; Barthélemy, Ernest J.; Zabala, Joaquín Pérez; Chemate, Sachin; Cain, Sarah; Lippa, Laura; Arendse, Tracey; Servadei, Franco; Kolias, Angelos; Rohlwink, Ursula K.; Esene, Ignatius N.; WFNS Young Neurosurgeons Committee (WFNS Journal, 2025)
The largest neurosurgical disease burden is found within low-and-middle-income countries. Despite this, a gap exists between the burden of disease and research output. This study explored the global neurosurgical research environment, with regards to capacity and output. We also explored the structural barriers to conducting research.In this cross-sectional survey, we examined the global neurosurgical research environment by collecting data from neurosurgeons and trainees from six continental regions. The survey was conducted in five languages and stratified to the following themes: demographics, research capacity, research output, and barriers to participating in research.A total of 565 responses were received, and participants were split equally across trainees and consultants. The median years of practice was 8 years, and 60.2% of respondents worked at government hospitals with a university affiliation. The research databases available reflect the current neurosurgical disease burden, although only 81.6% have science and ethics approval. The biggest barriers to conducting research were the availability of human resources (68.4%) and time (62.9%).The study reports on the current global neurosurgical research environment. The results show that the majority of neurosurgeons (98.2%) believe conducting research is important. Despite the challenges, there is a hunger to grow academic neurosurgery globally.
Keywords: education; global neurosurgery; research capacity; research equity; young neurosurgeons